Penerapan PSAK 23 dalam Penyusunan Laporan Keuangan pada CV Trio Bros Cakrawala - reynaldi surya saputra; Siti Rodiah SE.,M.Sc; Imelda Sahfitri; Delsa Yolanda putri; Nur Afriyanti (Politeknik Negeri Padang, 2025)
This article examines the application of Statement of Financial Accounting Standards (PSAK) 23 regarding revenue recognition at CV Trio Bros Cakrawala, a newly established company specializing in electronic equipment repair services located in Jl. Soebrantas, Perumahan BRP, behind RS Awal Bros Panam. The main objective of this study is to analyze how PSAK 23 is implemented in the preparation of the company’s financial statements, focusing on the process of revenue recognition, the responsibilities for recording, and the overall compliance with the standard. The research employs a qualitative approach through direct interviews with company representatives to gather in-depth information about their accounting practices. The findings reveal that revenue is recognized at the point of job completion and handover to the customer, which aligns with the accrual principle mandated by PSAK 23 for service revenues. However, the study also identifies that the company’s financial statements have not yet fully adopted all aspects of PSAK 23, primarily due to limited understanding and resources, as the business is less than a year old. The conclusion highlights the need for enhanced knowledge and systematic implementation of PSAK 23 to ensure accurate and reliable financial reporting in the future.